Sampling Rate Impact on Estimation of Untransposed Transmission Line Parameters Based on Fault Records - Costa, Eduardo C. M. da; Kurokawa, Sergio [UNESP]; Monaro, Renato M.; Di Santo, Silvio G. (Springer, 2018)
This paper highlights the sampling rate impact over an estimation method based on modal analysis techniques applied on untransposed three-phase transmission line. The analysed method represents a transmission system in the modal domain as three independent propagation modes that are modelled as three single-phase transmission lines using a suitable equivalent. The estimation procedure is carried out in the modal domain, without the explicit modelling of the phase mutual parameters, which means a significant simplification on the calculation process using the least-square solution method. Since the modal parameters are identified, the self- and mutual parameters can be calculated using the same modal transformation matrix during the line decoupling. The method estimation accuracy is evaluated for a range of sampling rate associated with the relays records.
Keywords: Sampling rate; Parameter estimation; Line parameters; Synchronized measurements; Fault records